2019
DOI: 10.1007/s42768-019-00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relationship between waste classification, combustion condition and dioxin emission from waste incineration

Abstract: Domestic waste in China is mainly collected as a combination of different types of materials. The components are variable and complex, with very different combustion characteristics making it difficult to optimize the burning to reduce pollution. There are still some controversies about the accuracy of using carbon monoxide (CO) emission to characterize waste incineration performance. Here, we investigated the relationship between waste classification, incineration conditions and dioxin emission and concluded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Qi et al ( 2018 ) found that many factories usually use incinerators for disposing of medical waste, which is sufficiently effective in the treatment of COVID-19 waste. While Li et al ( 2019 ) enlightens the fact that some factories do not use gas cleaners in their incinerators due to which many gasses such as dioxin get produced which causes human cancer, deformation in newborns, and also disturbs flora and fauna of environment. Apart from this, the medical waste also contains a recyclable portion; it is necessary to focus on recycling by chemical disinfection or sterilization processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qi et al ( 2018 ) found that many factories usually use incinerators for disposing of medical waste, which is sufficiently effective in the treatment of COVID-19 waste. While Li et al ( 2019 ) enlightens the fact that some factories do not use gas cleaners in their incinerators due to which many gasses such as dioxin get produced which causes human cancer, deformation in newborns, and also disturbs flora and fauna of environment. Apart from this, the medical waste also contains a recyclable portion; it is necessary to focus on recycling by chemical disinfection or sterilization processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presence of microplastics within the food chain poses a serious threat to the food safety and public welfare [7]. The incineration of plastic wastes, if not properly controlled and monitored, is likely to produce harmful byproducts, e.g., hydrochloric acid and dioxin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, waste- incineration plants presents challenges not traditional addressed, as combustion involves complex to model dynamical behaviour, with high uncertainty about the composition of the waste input. Specifically, inhomogeneous waste inputs [8] (e.g., uncertainty in qualitative characteristics such as calorific and moisture content of waste [9], [10]) cannot be determined a priori, and results in challenging to model combustion events, e.g., flame stagnation.…”
Section: Introductionmentioning
confidence: 99%